Pakistan : Household Use of Commercial Energy - Kojima, Masami (World Bank, Washington, DC, 2014)
This study aimed to examine the impact of changing availability of different energy sources and their price levels on household energy choice, consumption, and expenditures. Knowledge of household expenditures and energy consumption patterns is an essential building block for further work on possible policies in the energy sector and associated poverty and social impact analysis. To this end, the four most recent household expenditure surveys-conducted in 1994, 1997, 1999, and 2001-were analyzed in detail. The survey periods included those with low fuel prices (1999) and a time of rising world oil prices (2001). No household expenditure surveys are available from the last two years, when the increase in fuel prices has far outstripped general inflation. Nevertheless, between 1994 and 2001, prices of electricity, natural gas, kerosene, and liquefied petroleum gas (LPG) rose more rapidly than the consumer price index (CPI), potentially offering insights into how households might react to, and manage, sharply rising energy prices. The household survey analysis was supplemented by focus group discussions and individual interviews conducted in 2004 and 2005. Participants were asked questions about reasons for energy choice, the quality of service provided, evidence of increasing competition, affordability of different energy sources, benefits and costs, and commercial malpractice.